Insights for Stratification of Risk in Brugada Syndrome - Daniel García Iglesias (Radcliffe Medical Media, 2019)
Brugada syndrome (BrS) is an inherited disease with an increased risk of sudden cardiac death (SCD). However, testing identifies genetic disorders in only 20–30% of patients analysed, indicating a gap in knowledge of its genetic aetiology. Diagnosis relies on ECG, and risk stratification in BrS patients is challenging, primarily because of the complexity of the issue. As a result, clinicians fail to provide the appropriate strategy for SCD prevention for many patients. Several variables and interventions are being studied to improve diagnostics and maximise patient protection. In addition, the scientific community must increase efforts to provide patient care according to knowledge and research for improving stratification of risk. In this article, the authors summarise contemporary evidence on clinical variables and provide an overview of future directions in risk stratification and SCD prevention.